2021
DOI: 10.1002/ncp.10661
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative immunonutrition and carbohydrate loading associated with improved bowel function after radical cystectomy

Abstract: Background: Preoperative malnourishment has been consistently associated with poor outcomes after radical cystectomy and other major abdominal surgeries. Most enhanced recovery after surgery (ERAS) studies have examined preoperative nutrition and its relationship to outcomes after gastrointestinal surgery.Although numerous studies have demonstrated the benefits of using an ERAS protocol, this study in unique in comparing 2 ERAS protocols, with and without a nutrition component. Methods: A formalized preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Conventional preoperative fasting aims to minimize the risk of pulmonary aspiration but increases catabolic shift and acute-phase inflammatory markers [16]. Evidence suggests the beneficial effects of preoperative CHO loading on reducing IR [10] and cytokine levels [17] and improving bowel function [18]; however, the impact of preoperative CHO loading on postoperative NLR as an inflammatory and immunology-based predictor remains unclear. CHO, preoperative carbohydrate loading group; WBC, white blood cell; SD, standard deviation; Preop, 06:00 h on the day of surgery; POD1, 06:00 h on postoperative day 1; POD3, 06:00 h on postoperative day 3; POD5, 06:00 h on postoperative day 5; NLR, neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional preoperative fasting aims to minimize the risk of pulmonary aspiration but increases catabolic shift and acute-phase inflammatory markers [16]. Evidence suggests the beneficial effects of preoperative CHO loading on reducing IR [10] and cytokine levels [17] and improving bowel function [18]; however, the impact of preoperative CHO loading on postoperative NLR as an inflammatory and immunology-based predictor remains unclear. CHO, preoperative carbohydrate loading group; WBC, white blood cell; SD, standard deviation; Preop, 06:00 h on the day of surgery; POD1, 06:00 h on postoperative day 1; POD3, 06:00 h on postoperative day 3; POD5, 06:00 h on postoperative day 5; NLR, neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional preoperative fasting aims to minimize the risk of pulmonary aspiration but increases catabolic shift and acute-phase inflammatory markers [16]. Evidence suggests the beneficial effects of preoperative CHO loading on reducing IR [10] and cytokine levels [17] and improving bowel function [18]; however, the impact of preoperative CHO loading on postoperative NLR as an inflammatory and immunology-based predictor remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, there have been only few reports on the effectiveness of immunonutrition in MIBC and in small-sized or retrospective studies. [7][8][9][10] In 2021, Khaleel et al reported in a relatively large number of cases (n = 204) that intake of IMPACT for 5 days before surgery signi cantly reduced postoperative infectious complications after radical cystectomy and urinary diversion. 11 Our study also showed that preoperative intake of IMPACT signi cantly reduced the incidence of SSI.…”
Section: Discussionmentioning
confidence: 99%
“…54 Another study by Patel and colleagues comparing preoperative IMN to carbohydrate loading demonstrated earlier return of bowel function with IMN (3.12 vs. 3.74, p = 0.003) but did not demonstrate significant differences in other postoperative outcomes. 55 The Southwest Oncology Group (SWOG) S1600 Randomized Phase III clinical trial recently closed accrual and is investigating the effectiveness of IMN in patients undergoing RC with the primary endpoint being 30-day complications. 56 The study enrolled 200 patients and randomized 1:1 to either IMN or standard of care.…”
Section: Supplementationmentioning
confidence: 99%